Total mercury contamination in fish species of Northwestern Ecuador and potential human health risks - Gabriela S. Yánez-Jácome; Andrés Merino-Viteri; Eduardo Rebolledo Monsalve; Roberto Xavier Supe Tulcan; Laurence Maurice; Hugo Navarrete (PLoS ONE, 2026)
Gold mining activities are often suspected to increase mercury pollution-associated with human health and ecological risks in aquatic ecosystems. The objective of this study was to quantify total mercury (THg) concentrations in fish from four different sampling sectors along the Cayapas River watershed that varied according to different exposure levels to artisanal and small-scale gold mining (ASGM) activities. We analyzed 142 samples from eight freshwater fish species ( Bryconamericus dahli , Brycon sp. , Brycon dentex, Chaetostoma marginatum , Pimelodella modestus , Rhamdia quelen , Gobiomorus maculatus , and Mesoheros festae ). Potential human exposure and health risks from fish consumption in three population groups (children, women, and men) was also evaluated to estimate intake rates and determine fish consumption with minimal risk to the population’s health. We found different THg concentrations among feeding habits and sampling sectors. Carnivorous fish species ( Pimelodella modestus , Rhamdia quelen , Gobiomorus maculatus , and Mesoheros festae ) showed higher THg concentrations (0.063 ± 0.021 µg.g -1 ) and periphyton-feeder species ( Chaetostoma marginatum ) revealed the lowest levels (0.018 ± 0.007 µg.g -1 ). Downstream sites showed the highest levels of THg compared to the other upstream sites, despite some sites being directly impacted by ASGM activities. Regarding human exposure, no significant potential health risk was found for the exposed population over a lifetime. However, the THg of a Rhamdia quelen sample slightly exceeded the FDA-EPA Hg reference value in fish across all sites, representing a potential risk for children. Our results suggest that the THg concentrations in the studied fish species are independent of ASGM activities. The accumulation rates may be due to other parameters such as land uses, local hydrology, fishing pressure or natural habitats modification. Further ecological and physiological studies, including spatial and seasonal distribution of Hg in the surface sediment, water column and fish species, should be investigated to assess and modulate the impacts of the ASGM in the Santiago-Cayapas watershed compared with other land uses that contribute to the Hg inputs, bioaccumulation, and biomagnification in ichthyofauna.